Osteomyelitis therapy with hyperbaric oxygen: Terapi osteomielitis dengan oksigen hiperbarik - Hendri Poernomo (Makassar Dental Journal PDGI Makassar, 2022)
Osteomyelitis is a diffuse inflammation that affects the periosteum, cortical bone, and cancellous bone components. The inside of the bone that has been infected will become soft and experience swelling which causes the tissue to press against the outer wall of the bone and the blood vessels in the marrow whichcauses blood flow and oxygen supply to the bone decrease drastically. Usually surgical therapy is needed to treat osteomyelitis, but if the patient's physical condition does not allow it, hyperbaric oxy-gen therapy can be done to increase the supply of oxygen to the hypoxic bones. Hyperbaric oxygen therapy is an adjunctto conven-tional antibiotic or surgical treatment of resistant osteomyelitis, using large, multiposition or monoposition pressure tubes for one patient. The patients are given 100% oxygen with a pressure dose of 2-2.4 Atm for 90-120 minutes per day; five or six times per week for 8 weeks or more. Overall usage ranges from 80 to over 130 hours.